Peningkatan Pengetahuan tentang Cara Melakukan Latihan Fisik atau Olah Raga yang Aman Bagi Penderita Diabetes Mellitus - Dwi Rosella Komalasari; Arif Pristianto (Warta LPM, 2023)
Diabetes mellitus is a progressive chronic disease. DM is a disease with the category of non-communicable disease or a disease that is not caused by an infectious disease. Prolonged hyperglycemia has an impact on the development of microvascular and macrovascular complications, resulting in various problems, dissability and decreased quality of life. Regular and safe physical exercise is a therapy that can reduce glucose. However, not all people with diabetes are allowed to exercise. There are several provisions that must be observed to avoid side effects after exercise, such as hypoglycemia. Because DM is a disease with metabolic disorders, it is possible for patients to have complications, such as hypertension and coronary heart disease as common complications of DM. Not all people with DM understand the provisions that must be considered before doing exercise. Therefore, counselling is the most appropriate activity to provide information to patients with DM about the provisions that have to be considered before exercising. Counselling activities are expected to be followed up by patients with DM to do physical exercise or sports regularly and pay attention to their own condition. So that it can reduce the risk of developing DM and its complications and improve the quality of life of patients with DM.